2020
DOI: 10.33086/jhs.v13i01.1146
|View full text |Cite
|
Sign up to set email alerts
|

Karakteristik Penderita Glaukoma di Rumah Sakit Muhammadiyah Palembang Periode Januari 2017-April 2018

Abstract: Glaukoma merupakan penyakit mata di mana terjadinya kerusakan saraf optik yang disebabkan oleh hambatan pengeluaran cairan bola mata (Humour Aquous). Glaukoma merupakan penyebab kebutaan terbanyak setelah katarak. Penelitian ini bertujuan untuk mengetahui karakteristik penderita glaukoma di Rumah Sakit Muhammadiyah Palembang periode Januari 2017 – April 2018 berdasarkan usia, jenis kelamin, jenis glaukoma, keluhan utama, tekanan intraokular, dan riwayat penyakit sebelumnya. Penelitian ini menggunakan desain pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…Based Guede's study, age >60 years with history of diabetic retinopathy has increased intraocular pressure compared to age <60 years and is a risk factor for glaucoma. 10 This is because with age, the flow of aqueous humor decreases and the ciliary epithelial cell structure changes due to the aging process, resulting in an increase in intraocular pressure. 11 This is consistent with previous research which states that the higher a person's age, the higher the average intraocular pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Based Guede's study, age >60 years with history of diabetic retinopathy has increased intraocular pressure compared to age <60 years and is a risk factor for glaucoma. 10 This is because with age, the flow of aqueous humor decreases and the ciliary epithelial cell structure changes due to the aging process, resulting in an increase in intraocular pressure. 11 This is consistent with previous research which states that the higher a person's age, the higher the average intraocular pressure.…”
Section: Discussionmentioning
confidence: 99%
“…The results of other studies showed that intraocular pressure >21 mmHg was more common than intraocular pressure <21 mmHg (normal) (Dizayang et al 2019). Glaucoma patients generally had a high intraocular pressure, except in normal-tension glaucoma.…”
Section: Intraocular Pressurementioning
confidence: 91%
“…Hashemi et al (2019) showed that 57.1% of glaucoma patiens were women and 42.9% were men. Meanwhile, Dizayang et al (2019) showed that the majority of primary glaucoma patients were women (57.8%)…”
Section: Gendermentioning
confidence: 99%
“…Hasil penelitian ini memiliki kesesuaian jenis keluhan yang disampaikan pada studi lainnya, bahwa pada penderita glaukoma didapatkan keluhan utama pasien mencakup nyeri mata sebesar 37,7%, mata kabur sebesar 29,5%, sakit kepala dengan persentase 14,8% dan buta sebesar 9,8%. 20 Glaukoma primer sudut terbuka sebagian besar bersifat asimptomatik. Gejala klinis mulai disadari ketika terjadi perburukan kondisi mata penderita sehingga penderita datang sudah dengan tajam penglihatan yang buruk.…”
Section: Pembahasanunclassified